Design of a Dual Band Antenna for Wireless Communications Utilizing the Sierpinski Carpet Fractal - Attioui Sanae; Khabba Asma; Ibnyaich Saida; Zeroual Abdelouhab (ITM Web of Conferences)
This study is focused on the design and presentation of a unique dual band fractal antenna that incorporates the Sierpinski carpet onto the fundamental rectangular patch antenna. The versatility of this fractal antenna lies in its innovative design, which makes it suitable for the applications that operate in the C-band and X-band. The process of producing the Sierpinski carpet involves cutting three squares of different sizes within the given patch area. The fractal antenna that is suggested is placed on a substrate composed of FR-4 material, which possesses a dielectric constant of 4.4. Additionally, the antenna has dimensions 35 × 30 × 1.6 mm3. The antenna that is being proposed for use has been designed and developed through the utilization of the High-Frequency Structure Simulator (HFSS). According to the simulation results, it can be observed that the fractal antenna demonstrates the capability of resonating at three distinct frequencies. The frequencies of 4.88 GHz (-19.88 dB), 9.62 GHz (-15.07 dB), and 10.03 GHz (-26.65 dB) are all characterized by a radiation behavior that is considered appropriate for the intended application.